Using a Commercial Framework to Implement and Enhance the IEEE 1451.1 Standard - Viegas, Vítor (2005)
In 1999, the 1451.1 Std was published defining a common object model and interface specification to develop open, multi-vendor distributed measurement and control systems. However, despite the well-known advantages of the model, few have been the initiatives to implement it. In this paper we describe the implementation of a NCAP – Network Capable Application Processor, in a well-known and well-proven infrastructure: the Microsoft .NET Framework. The choice of a commercial framework was part of our strategy: to take advantage of several “of the shelf” technologies and adapt them to produce a NCAP prototype, called NCAP/XML. In addition, a solution to enhance the 1451.1 Std is presented by proposing a new format for inter-NCAP communication based on XML (eXtended Markup Language).